La quinua en el Ecuador situación actual y su industrialización - Cuadrado Alvear, Silvana Alejandra (2012)
The present research, a study of the current situation of quinoa in Ecuador and its industrialization. The purpose that guided this research was: Contextualizing past, present and future production, demand and domestic consumption of quinoa in our country, analyzing the possibilities of industrialization. The theoretical framework contains content on the productivity and competitiveness in economic thinking, analyzing the Porter´s theory competitiveness. In the conceptual framework are developed important concepts that are mentioned throughout this paper as: productivity, competitiveness, food security and industrialization